(t+33)+(t+11)=4t-9

Simple and best practice solution for (t+33)+(t+11)=4t-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t+33)+(t+11)=4t-9 equation:


Simplifying
(t + 33) + (t + 11) = 4t + -9

Reorder the terms:
(33 + t) + (t + 11) = 4t + -9

Remove parenthesis around (33 + t)
33 + t + (t + 11) = 4t + -9

Reorder the terms:
33 + t + (11 + t) = 4t + -9

Remove parenthesis around (11 + t)
33 + t + 11 + t = 4t + -9

Reorder the terms:
33 + 11 + t + t = 4t + -9

Combine like terms: 33 + 11 = 44
44 + t + t = 4t + -9

Combine like terms: t + t = 2t
44 + 2t = 4t + -9

Reorder the terms:
44 + 2t = -9 + 4t

Solving
44 + 2t = -9 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
44 + 2t + -4t = -9 + 4t + -4t

Combine like terms: 2t + -4t = -2t
44 + -2t = -9 + 4t + -4t

Combine like terms: 4t + -4t = 0
44 + -2t = -9 + 0
44 + -2t = -9

Add '-44' to each side of the equation.
44 + -44 + -2t = -9 + -44

Combine like terms: 44 + -44 = 0
0 + -2t = -9 + -44
-2t = -9 + -44

Combine like terms: -9 + -44 = -53
-2t = -53

Divide each side by '-2'.
t = 26.5

Simplifying
t = 26.5

See similar equations:

| 12-4y=6 | | s-4t=29 | | 4(6+2x)=2(x-3) | | 5(4-y)=20 | | 17-3x=2+3x | | 60-4t= | | y=-x^2-6x+4 | | s-4t= | | 1-2x=1-3y | | 3*0-4*y=6 | | 0.63+0.24t=2.68t-1.20 | | 33u-50+u+29=29u | | -8w^2+18w-9=0 | | 6(y-1)-4=-4(-6y+3)-4y | | 2y+2(y-8)=6y-4(y-10) | | 8x^2+16x=192 | | 39q+19+30=44q+45 | | 0=-16t^2+150t+30 | | x^2-49x+500=0 | | 6a-47+30=5a | | y+3-2(-8y-3)=7(y-1) | | 3.8x-4.7=3.8x+17.5 | | 19-12x=151 | | 2a+36=4a-14 | | 2.67x+3x=102 | | (x-2)2+(y-4)2=36expand | | 5x+10=-26 | | 34616.0131=B*45.3 | | ln(4x)+1=3 | | (v+39)+5v=11v-36 | | 3679.6530=171.9464*h | | 5k-12=-22 |

Equations solver categories